Calculation of Blasting Damage Zone Radius of Different Charge Structures in Burnt Rock - Zhengzhao Jia; Hongjie Li; Wei Li; Jie Yan (Applied Sciences)
The radius of the failure area after a blasting fracture process of burnt rock is affected by joint fissures, does not conform to the existing theoretical calculation formula and the distribution law of the failure area also changes. The fracture area is large, and the fracture extension and expansion area are small. Therefore, in order to describe the damage of blasting to a fractured rock mass more objectively and accurately, on the basis of summarizing the previous research results, a damage variable was introduced to characterize the initial crushing degree of the fractured rock mass, and the corresponding rock failure criterion was used to derive the calculation formula of a blasting crushing circle and fracture circle radius of burnt rock with different charge structures. The results show that the blasting failure zone of fractured rock mass with different charge structures was not only related to the radius of the blast hole and the explosive and rock properties, but also had a strong relationship with the initial damage degree of the rock mass. Taking an open-pit coal mine in Xinjiang as an example, the radius of the fracture zone with different charge structures was obtained by using the obtained calculation formula, and it was applied to the determination of row spacing and hole spacing.